Antibacterial Activity of Origanum Syriacum L. Essential Oil against Some Pathogenic Bacteria - Ismail, Imad; Abbas, Nora (Latakia University Journal -Biological Sciences Series, 2013)
A field survey of Pepper mild mottle (PMMV) and Cucumber mosaic (CMV) Viruses was conducted in some plantation areas in Tartous and Lattakia Provinces. A total of 1278 samples (782 from Tartous and 505 from Lattakia) were collected. Results of Tissue Blot Immunobinding Assay showed the presence of PMMV in 0.39% and CMV in 11.42% in the collected samples. The percentage of CMV varied in Tartous and Lattakia Provinces. In this study, PMMV was not recorded in Lattakia, whereas it was recorded in Tartous in a small percentage (0.64%). Using Tissue Blot Immunobinding Assay, the collected seeds from the infected pepper fruits from Tartous fields showed the transmission of PPMV throughseeds in a ratio of 0.70% to 0.87% according to seed resources, whereas CMV was transmitted in a high percentage of 2.81% to 7.98% according to seed resources. PPMV was not recorded in leaf samples or in seeds taken from Blozah District in TartousProvince.